La construction politique de la commune mesure de la qualité des eaux superficielles en France : de l’équivalent-habitant au bon état (1959-2013) - Gabrielle Bouleau; Pierre-Luc Marchal; Michel Meybeck; Laurence Lestel (Développement Durable et Territoires)
Public authorities in charge of preparing and implementing the 1964 French water law and the 2000 European Water framework Directive similarly relied on inventories. In order to justify public action, they needed to objectify a situation which was either poorly known or informed by heterogeneous criteria. We show that political considerations are embedded in the indicators and the monitoring network of both inventories. They pertain to the type of realism which allows comparisons, shapes the frontiers of public policy, legitimates uses of water, and defines the sharing of restoration’s financial burden. We compare the controversies that rose during both inventories’ construction to conclude on their political meaning.